(untitled) (Research, Society and Development, 2021)
Objective: To describe the main risk factors for the development of cervical cancer, emphasizing HPV infection and the relevance of immunization in the prevention of cervical cancer, in addition to discussing immunological aspects and the main diagnostic methods. Methodology: A descriptive literature review was carried out, with a qualitative character, using materials indexed on the PubMed, SciELO platforms and on the CAPES journals portal, after searching and applying the inclusion and exclusion criteria, a total of 52 files were selected, published between 2010 and 2020 and written in the languages: Portuguese, English and Spanish. Results and Discussion: The cases of cervical cancer have HPV infections as the main factor. Still, the following can also be mentioned: infections by the Herpes simplex virus type II, the use of corticosteroids, multiple partners, smoking, low vitamin intake, low socioeconomic status, use of contraceptives, homosexual and bisexual practices, early onset of activity sexual intercourse, immunosuppression, multiparity and Chlamydia trachomatis infections. Conclusion: In summary, based on the scientific instruments used, the various factors associated with cervical cancer were demonstrated. In contrast, the prevention of HPV infections through vaccination is an important tool for reducing the chances of future complications.